Community-Based Kitchen Wastewater Management: Assessing Knowledge and Attitudes towards Simple Eco-Friendly Grease Trap (GASTDAR) Design - A Case Study along Bincau Irrigation Embankment: Pengelolaan Limbah Cair Dapur Berbasis Masyarakat: Evaluasi Pengetahuan dan Sikap terhadap Desain Perangkap Lemak Ramah Lingkungan (GASTDAR)- Studi Kasus di sepanjang Bantaran Irigasi Bincau - Tien Zubaidah; Sulaiman Hamzani; Arifin Arifin (Universitas Lancang Kuning, 2023)
Kitchen wastewater management near Bincau Irrigation Embankment is a major environmental issue. To address this concern, we held a community engagement program to teach wastewater management and install a floating, four-chamber Simple Grease Trap (GASTDAR). Fats, oils, Total Suspended Solids (TSS), and Chemical Oxygen Demand were measured before and after GASTDAR deployment to assess water quality. GASTDAR decreased lipids and oils 64.3%, TSS 53.7%, and COD 55.7%. Restaurant owners and employees' wastewater management knowledge and attitudes increased dramatically. Finally, GASTAR's unique design reduced the environmental impact of kitchen wastewater, improving the water ecosystem near the Bincau Irrigation Embankment.